Correlation of Sunspot Numbers and Geomagnetic Indices with Various Climate Change Parameters - Adhikari, S.; Mishra, R. K.; Parajuli, N.; Adhikari, D. P.; Adhikari, B. (Journal of Nepal Physical Society, 2023)
In this paper, a comparative study of climate change parameters with the sunspots number, solar flux, and various geomagnetic indices are presented using statistical methods, cross-correlation analysis and Continuous Wavelet Transform (CWT). From the analysis of 31 years (almost 3 solar cycles) datasets, we observed a positive correlation of sunspot numbers with geomagnetic indices such as AE, Kp, Ap, Dst, and pc. This analysis indicates that variation in sunspot numbers can have a strong influence on the geomagnetic configuration. We also a found perfect positive correlation between CO2 -CH4 and CO2 – TSI, shown with a correlation coefficient of approximately 1 at 0-time lag. The sunspot number shows a high positive correlation with solar flux with a correlation coefficient of 0.95 at 0-time lag indicating that the earth is receiving energy from the sun, which is small but not a negligible fraction of expected global warming. The wavelet analysis carried out on sunspot number (R), Methane emission (CH4), Carbon dioxide emission (CO2), Land-Ocean Temperature (LOT), Solar Flux (F10), and, Total Solar Irradiance (TSI) support the evidence of ~11 years of periodicities. Both analyses suggested that the recent climate change is mostly affected by anthropogenic forcing (long-lived greenhouse gases) followed by natural forcing (sunspot number) which cannot be neglected. Thus, the correlation and wavelet analysis suggest that the sun also has a significant role in climate change, and, understanding the role of solar variability is essential to the interpretation of past and prediction of future climate.